Russian Consensus: Standardization of Indications for Surgical Treatment of GERD - I. Ye. Khatkov; D. S. Bordin; O. S. Vasnev; S. R. Abdulkhakov; A. S. Allakhverdyan; D. N. Andreev; V. V. Anishchenko; I. G. Bakulin; N. V. Bakulina; M. V. Burmistrov; E. R. Valitova; D. I. Vasilevsky; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
Aim: to present the results of an Expert Consensus on standardization of indications for surgical treatment of gastroesophageal reflux disease (GERD). Materials and methods. The issues of standardization of indications for surgical treatment of GERD were discussed by 39 experts – leading gastroenterologists and surgeons from 7 cities of Russia, representing 17 institutions. The list of questions for discussion was formed by the initiative group and sent to the experts. The experts reviewed recent literature, including existing clinical guidelines and consensuses, assessed the evidence base and suggested statements for voting based on the analysis of relevant provisions of foreign consensuses, high-level scientific publications, which set out information obtained in the course of studies that meet the criteria of evidence-based medicine, positions on this issue in the Russian Federation, and suggested statements for voting. Delphi method was used to reach the consensus.Results. GERD is the most common benign esophageal disorder. Surgery is considered one of the treatment methods for GERD. In real clinical practice, selection of patients who may benefit from surgery is challenging. The results of surgical and conservative treatment of GERD are comparable. Surgical treatment should be performed in a specialized hospital only after a joint examination with a gastroenterologist confirming the diagnosis of GERD. An appropriate volume of preoperative diagnostic workup, matters related to surgical interventions in case of incomplete response to proton pump inhibitors (PPIs) and when extraesophageal manifestations of GERD are present were discussed. The consensus reviews the indications, contraindications and possible results of antireflux operations in patients with GERD. The value of endoscopy, esophageal manometry, pH monitoring/pH-impedance monitoring and X-ray polypositional examination of the upper gastrointestinal tract as a preoperative examination of the patient is analysed. Conclusions. The experts reached the consensus on 20 statements on standardization of indications for surgical treatment of GERD.